Barriers and facilitators to HIV viral load suppression among adolescents living with HIV in Lubumbashi, Democratic Republic of the Congo: A qualitative study - Olivier Mukuku; Kaymarlin Govender; Stanislas Okitotsho Wembonyama (PLoS ONE, 2025)
Background Antiretroviral therapy (ART) has been pivotal in improving the lives of adolescents living with HIV (ALHIV) globally. However, achieving and maintaining viral load suppression (VLS) among ALHIV remains a significant challenge, with difficulties reported in various settings, including places like Lubumbashi, in the Democratic Republic of the Congo. Despite the availability of ART, several barriers to optimal ART adherence and achieving VLS persist among this population. This qualitative study aimed to explore the factors influencing ART adherence and achieving VLS among ALHIV in Lubumbashi. Methods In-depth interviews were conducted with 39 ALHIV (22 female, 17 male) receiving ART and 14 caregivers (9 female, 5 male) participating in their treatment. ALHIV were purposively selected based on criteria including being HIV-positive, on ART, informed of their HIV status, and aged 13-19 years. Caregivers were purposively sampled based on their involvement in the treatment and care of the ALHIV. Focus group discussions were held with 16 healthcare workers (HCWs) (10 female, 6 male), including doctors, nurses, and pharmacists, who had at least one year of experience caring for ALHIV in the selected clinics. The sessions were audio-recorded, transcribed, and analyzed using a thematic approach to identify recurring themes and patterns. Data analysis was guided by the socioecological model, examining factors at the individual, interpersonal, health service-related, and community levels. NVivo 14 software was used for data management and analysis. Results The key barriers to achieving VLS identified included economic challenges, stigma and discrimination, forgetfulness, and a lack of family support. Factors such as strong social support, regular counseling, use of reminder tools, and positive HCW-patient relationships were found to facilitate ART adherence and achieving VLS. The participants emphasized the importance of addressing psychosocial challenges alongside medical treatment to improve outcomes for ALHIV. Conclusions Improving VLS among ALHIV in Lubumbashi requires a multifaceted approach that includes strengthening family and community support systems, simplifying ART regimens, and enhancing HCW capacity to offer comprehensive care. Policy interventions and collaborative efforts across sectors are essential to overcoming the barriers to ART adherence and achieving sustained VLS in this vulnerable population.